Reviewing the experience with the repatriation of sacred ceremonial objects: A comparative legal analysis of Canada and South Africa. Issue 3 (August 2022) - Ingelson, Allan; Owosuyi, Ifeoma
Abstract: Recent global interest in preserving cultural identity and heritage for the future of previously colonized Indigenous groups has prompted the resuscitation of local and Indigenous cultures from the brink of extinction. The pertinence of protecting and managing cultural heritage as an endowment that transcends generations of people and serves as a ligature between their past, present, and future cannot be overstated. In this respect, the repatriation or restitution of sacred ceremonial objects (SCOs) and cultural artifacts constitutes an integral aspect of reviving Indigenous people's cultural and living heritage, which has been eroded by colonialism and other forms of occupation. In Alberta, Canada, the First Nations Sacred Ceremonial Objects Repatriation Act is the foremost legislation that provides a formal mechanism for the return of SCOs to the First Nations. Thus far, it has successfully facilitated the repatriation of several hundred repatriated several SCOs. In contrast, South Africa's primary heritage legislation, the National Heritage Resources Act, lacks direction and detail on the restitution of SCOs, specifically to cultural communities. With the aid of a comparative approach, this article critically examines one successful approach to the repatriation of specific sets of heritage objects in Canada and analyzes South Africa's legal frameworks that consider SCOs as a component of its national estate within its framework for restitution and the promotion of cultural revival in cultural communities.